DID PUBLIC CASH TRANSFER CROWD OUT INTER-HOUSEHOLD TRANSFERS IN INDONESIA? EVIDENCE FROM "BANTUAN LANGSUNG TUNAI /BLT" - Wulandari, Corry; Baryshnikova, Nadezhda (JURNAL INFO ARTHA, 2019)
In 2005 the Government of Indonesia introduced an unconditional cash transfer program called the ‘Bantuan Langsung Tunai’ (BLT), aimed at assisting poor people who were suffering from the removal of a fuel subsidy. There are concerns, however, that the introduction of a public transfer system can negatively affect inter-household transfers through the crowding-out effect, which exists when donor households reduce the amount of their transfers in line with public transfers received from the government. The poor may not therefore have received any meaningful impact from the public cash transfer, as they potentially receive fewer transfers from inter-household private donors. For the government to design a public transfer system, it is necessary to properly understand the dynamics of private transfer behaviour. Hence, this study evaluates whether there exists a crowding-out effect of public transfers on inter-household transfers in Indonesia.Using data from the Indonesia Family Life Survey (IFLS) and by applying Coarsened Exact Matching (CEM) and Difference-in-differences (DID) approaches, this study found that the likelihood to receive transfers from other family members (non-co-resident) reduces when the household receives BLT. However, there is no significant impact of BLT on transfers from parents and friends.